ANALISIS ERGONOMI PADA POSTUR DUDUK SISWA MENGGUNAKAN METODE QUICK EXPOSURE CHECK - Diansari, Brillian Nur; Saputro, Fery Wisnu; Wijaya, Sandy Danu (TEKNIKA: Jurnal Teknik, 2023)
Ergonomics is a science that studies interactions between humans and system elements based on human strengths and limitations. One of the applications of ergonomics is the interaction between students and learning facilities. Students study at school for more than 8 hours with sitting for their dominant activity. Not ergonomics sitting posture, such as: bending over, tilting to one side, supporting the chin, resting the chin on the table and bending the neck can cause the risk of Musculoskeletal Disorders (MSDs). Currently, students have complaints of pain in the neck and lower back. Therefore, this research aim is analyzing unergonomics sitting posture of student from an ergonomics perspective to avoid the risk of Musculoskeletal Disorders (MSDs). The method used in this research is Quick Exposure Check (QEC), which is generally used to detect fatigue and musculoskeletal disorders in workers, but as an innovation this method is used to analyze the phenomenon of students sitting posture. The assessment using this method produces an Exposure Score of 61,73%, it means that further research and improvement are needed in this condition. So, it is recommended that students have to sitting in ergonomics posture to avoid the risk of musculoskeletal disorders, creating an effective, comfort, safe, and efficient learning conditions and improving the quality of learning. Keywords: Students, Assessment, Improvement